Passaporte ou álcool em gel?: um estudo sobre a percepção de risco de contágio e a intenção de viajar na pandemia do Covid-19 - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The covid-19 pandemic has severely impacted the tourism sector, as to contain the contamination and spread of the virus, personal distancing and the closing of borders were imposed, thus hindering consumers to benefit from such activity. Thus, considering the measures imposed regarding the advancing of the pandemic and its impacts on tourism, this study aimed to identify the relationship between the perception of risk of contamination and the intention to travel in the face of the Covid-19 pandemic. Therefore, a quantitative and descriptive research was carried out, using the survey method, which had a sample of 542 respondents. Data analysis was carried out with descriptive statistics, correlation test, and independent sample tests to analyze the perceptions of the variables: having contracted the virus; if one has lost a dear to illness; the gender of the respondents, and; if they belong to the risk group. The main results found were: the greater the perception of risk of contamination, the lower the intention to travel; people who have not been contaminated tend to have a greater perception of risk; men tend to have more intention to travel than women, however, women perceive a greater risk of contamination; and those who have lost someone to the virus have a greater perception of risk.
Passport or alcohol gel sanitizer?: a study on the perception of risk of contagion and the intention to travel in the Covid-19 pandemic
¿Pasaporte o alcohol en gel?: un estudio sobre la percepción de riesgo de contagio y la intención de viajar en la pandemia del Covid-19
Keywords: Pandemia; Intenção de viajar; Percepção de risco; Comportamento do consumidor; Pandemic; Intention to travel; Risk perception; Consumer behavior; Intención de viajar; Percepción del riesgo; Comportamiento del consumidor; CNPQ::CIENCIAS SOCIAIS APLICADAS